FACTORS INFLUENCING CONSUMER DECISIONS IN PURCHASING LOCAL FRUIT AT RAYA MEDAN MARKET, METRO TRADE CENTRE - Octaviani Panjaitan; Syahbudin Hasibuan; Sri Ariani Safitri (Journal of Agri Socio Economics and Business, 2023)
Local fruit is fruit grown by local farmers throughout Indonesia. There are 3 local fruits, namely bananas, Siamese oranges and mangoes at Raya Medan Market, Metro Trade Center (MMTC) which is a traditional market and is managed by a private company, namely PT. Deli Metropolitan on 7 hectares of land. This study aims to analyze: 1) The process of consumer decision making in purchasing local fruit at  MMTC’s  Raya Market. 2) Factors that influence the decision to buy local fruit at  MMTC’s  Raya Market. This research was conducted in April 2022. The number of samples was 60 consumers of local fruit. The method used to determine the sample isNon Probability. Data analysis used Multiple Linear Regression by conducting two tests, namely the research instrument test and the hypothesis test. The results of the study show that: 1) The decision making process in buying local fruit goes through several stages, namely need recognition, information search, selection of alternatives, purchasing decisions and post-purchase behavior 2) The test results show that price, product and location affects the purchase decision.